Clinical utility of correction factors for febrile young infants with traumatic lumbar punctures. Issue 6 (29th December 2020) - Rogers, Sarah; Gravel, Jocelyn; Anderson, Gregory; Papenburg, Jesse; Quach, Caroline; Burstein, Brett
Abstract: Objectives: Correction factors have been proposed for traumatic lumbar punctures (LPs) in febrile young infants. However, no studies have assessed their diagnostic utility. We sought to determine the proportion of traumatic LPs safely reclassified as low risk for bacterial meningitis using recently derived white blood cell (WBC) and protein correction factors. Methods: We retrospectively analyzed traumatic LPs among all febrile infants ≤60 days old at two tertiary paediatric hospitals from 2006 through 2018. Traumatic LPs were defined as ≥10, 000 RBCs/mm 3 . Abnormal cerebrospinal fluid (CSF) WBCs and protein were adjusted downward using a newly derived correction factor (877 red blood cells [RBCs]: 1 WBC), three commonly used correction factors (500 WBCs: 1 RBC; 1, 000 WBCs: 1 WBC; peripheral RBCs: WBCs), and a newly derived protein correction factor (1, 000 RBCs: 0.011 g/L protein). Results: There were 437 traumatic LPs including 357 (82%) with pleocytosis and 4 (0.9%) with bacterial meningitis. Overall, fewer infants were classified as having CSF pleocytosis using 877:1 and 1, 000:1 ratios (38% and 43%, respectively), with 100% sensitivity and negative predictive value, and improved specificity (63% for 877:1, 58% for 1, 000:1 ratios versus 19% for uncorrected counts). Among infants with pleocytosis, 877:1 and 1, 000:1 ratios reclassified 191 (54%) and 171 (48%) as normal with no misclassified bacterial meningitis cases. Ratios of 500:1 and peripheral RBC:WBC misclassified 1 infant that had bacterial meningitis. Corrected CSF protein outperformed uncorrected protein in specificity but did not add diagnostic value following WBC-based correction. Conclusions: Correction ratios of 877:1 and 1, 000:1 safely reclassified half of all febrile infants ≤60 days. These corrections should be considered when interpreting CSF results of traumatic LPs.